2022
DOI: 10.1109/taes.2021.3139559
|View full text |Cite
|
Sign up to set email alerts
|

Cybersecurity Attacks on Software Logic and Error Handling Within ADS-B Implementations: Systematic Testing of Resilience and Countermeasures

Abstract: Automatic Dependent Surveillance-Broadcast (ADS-B) is a cornerstone of the next-generation digital sky and is now mandated in several countries. However, there have been many reports of serious security vulnerabilities in the ADS-B architecture. In this paper, we demonstrate and evaluate the impact of multiple cyberattacks on ADS-B via remote radio frequency links that affected various network, processing, and display subsystems used within the ADS-B ecosystem.Overall we implemented and tested 12 cyberattacks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 31 publications
(36 reference statements)
2
22
0
Order By: Relevance
“…However, implementing a proper defense strategy requires more systematic research and development, which is beyond the core focus of this paper. Nonetheless, in a similar service in aviation (ADS-B), we showed a received signal strength (RSS) and distance relationship model [8] that reached up to 90% accuracy in the best case. This strategy can easily be transferred to AIS, as the concept is protocol agnostic.…”
Section: Defence Against Ais Attacksmentioning
confidence: 86%
See 1 more Smart Citation
“…However, implementing a proper defense strategy requires more systematic research and development, which is beyond the core focus of this paper. Nonetheless, in a similar service in aviation (ADS-B), we showed a received signal strength (RSS) and distance relationship model [8] that reached up to 90% accuracy in the best case. This strategy can easily be transferred to AIS, as the concept is protocol agnostic.…”
Section: Defence Against Ais Attacksmentioning
confidence: 86%
“…However, these types of portable receivers remain untested against cyberattacks, as shown in current literature. Lack of extensive study of AIS exploitation, insufficient study on the impact of cyberattacks on modern AIS setups, and our previous security experience on a similar aviation service (Automatic Dependent Surveillance-Broadcast (ADS-B) [7], [8]) have motivated us to conduct this study. Our aim is to enhance the early discovery of new vulnerabilities in AIS to effectively address AIS attacks in the nearest future.…”
mentioning
confidence: 99%
“…Secondly, the methodology for POA signal generation was made specifically for this study as student work, which promotes its release as a part of this master's thesis. Thirdly, the signal generation methodologies for the ADS-B and AIS protocols were developed by Khandker et al (2021Khandker et al ( , 2022, and are retained as proprietary intellectual property of the University of Jyväskylä researchers. Because these protocols are used in aircraft and vessel tracking, attacks against them carries comparatively far-reaching consequences.…”
Section: Signal Transmittance Chain Developmentmentioning
confidence: 99%
“…Any informed individual or group can implement these protocols for compatible transceivers. Previous research has demonstrated that spoofing and other advanced attacks are possible for ACARS [20], [21], [22], [23], [24], ADS-B [25], [26], [27], [28], and AIS [29], [30].…”
Section: B Mission-critical Wireless Protocolsmentioning
confidence: 99%
See 1 more Smart Citation